UMA PROPOSTA DE ENSINO DE ESTATÍSTICA UTILIZANDO A MODELAGEM MATEMÁTICA NO ENSINO MÉDIO. - OLIVEIRA, Patrícia Azevedo de (2019)
This work presents a research with a didactic-pedagogical approach in mathematical modeling, using the five modeling stages suggested by Burak and Aragão (2012), as support for the construction of didactic sequences used in the intervention phase through the accomplishment of experiments, whose objective was to analyze the didactic use of mathematical modeling in the resolution of statistical problems applied to the students of a 3rd year high school class of a public school in São Luís, MA. To support the theoretical discussions on the subject, studies by Barbosa (2004) were used; Almeida, Silva and Vertuan (2012); Burak and Aragon (2012); Meyer, Caldeira and Malheiros (2013); Bassanezi (2016); Biembengut (2016); Biembengut and Hein (2016); Alencar and Bueno (2017). It was a qualitative intervention research, aimed at the theoretical reflections on the appropriation of concepts on central tendency and dispersion measures, as well as the application of these measures in the resolution of statistical problems. The results revealed that the students appropriated the worked concepts as well as the statistical activities developed in the classroom. It was also observed that this methodology allowed them to develop new resolution heuristics, thus promoting learning of the object of study. However, the teaching proposal triggered the educational product that constituted a tutorial for the use of mathematical modeling in statistical experiments in Basic Education with four activities on statistical measures of centrality and dispersion, which were worked with the students surveyed. For this, four experiments were performed: the first two themes (World Cup; 2018 elections in Brazil) were presented by the researcher and the other two themes were chosen by the students, who suggested with greater emphasis two discussion topics: health and technology. Thus, the last two experiments addressed the themes (food diary; the use of GeoGebra in the treatment of information).